Conductive stretchable shape memory elastomers combining with electrical stimulation for synergistic osteogenic differentiation. (October 2020) - Yan, Huanhuan; Li, Linlong; Shi, Xincui; Yeh, Jui-Ming; Wei, Yen; Zhang, Peibiao
Abstract: The natural extracellular matrix (ECM) possessed varying biomechanical properties which played important roles in the dynamic cellular microenvironment. However, for the conventional bone tissue engineering scaffolds, stretchability and shape memory property were normally absent. Thus, the behaviors of responsive changes required in dynamic physiological settings were unsatisfactory. Herein, a series of conductive polyurethane shape memory elastomers (PCL-IPDI-AT) were synthesized, which based on conductive amino capped aniline trimer (AT), isophorone diisocyanate (IPDI) and poly(ԑ-caprolactone) (PCL). The conductive elastomers possessed high elasticity and flexibility, especially, the breaking elongation of copolymer with 15% AT content was up to 570 ± 56%. The mechanical properties of elastomers could be adjusted by regulating the content of AT in copolymers. The conductive elastomers exhibited excellent shape fixity ratio and good shape recovery ability at 37 °C. The electrical conductivity of elastomers was measured via the standard van der Pauw four-probe method. They were all around 10 −7  S/cm and similar to that in human physiological environments. On the one hand, excellent cytocompatibility was demonstrated by the viability and proliferation results of MC3T3-E1 pre-osteoblasts seeded on the elastomer. On the other hand, the elastomer could synergistically promote the osteogenic differentiation compared to PCL in terms of ALP activity, calcium deposition, and bone-related protein and gene expression levels as combined with electrical stimulation (ES). Specifically, the ALP activity for conductive elastomer under ES was notably improved by 1.4-fold compared to PCL at 7 days. Overall, the conductive elastomers displayed excellent stretchability, shape memory property, fatigue resistance and osteogenic bioactivity. They may be applied as bone substitutes for electrical-signal-sensitive bone tissue engineering. Graphical abstract: The conductive elastomers with excellent stretchability, shape memory property, fatigue resistance can synergistically enhance osteogenic differentiation combining with electrical stimulation. Image 1 Highlights: The conductive elastomers (PCL-IPDI-AT) were synthesized through a one-pot step-growth addition polymerization reaction. The electrical conductivity of elastomers was all around 10 −7 S/cm and similar to that in human physiological environments. The conductive elastomers with 15% AT content exhibited well mechanical properties and good shape recovery ability at 37 ℃. The conductive copolymer exhibited excellent cytocompatibility demonstrated by the viability and proliferation results. The conductive copolymer combining with ES could synergistically promote the osteogenic differentiation of MC3T3-E1 cells.